Implementation of a Web-Based Customer Relationship Management System to Enhance Customer Loyalty - Alfaraby, Feby; Alamsyah, Zaenal; Fergina, Anggun (Komunitas Dosen Indonesia, 2026)
Customer Relationship Management (CRM) plays a critical role in sustaining customer relationships, particularly within SMEs in the retail sector that depend on repeat purchases. This study aims to examine how the IDIC (Identify, Differentiate, Interact, and Customize) framework can be operationalized under SME resource constraints through the design and evaluation of a web-based CRM system. Using empirical transaction records collected during an operational period, the study adopts a design-oriented empirical approach combining system development with IDIC-based analytical evaluation. The primary research contribution lies in the conceptual operationalization of the IDIC framework into implementable CRM modules rather than in proposing a novel technical architecture. Customer identification is achieved through centralized customer records, while differentiation relies on transaction frequency as a pragmatic behavioral indicator of repeat purchasing. Interaction is facilitated through automated reminder notifications, and customization is intentionally bounded to personalized reminders derived from transaction histories. System effectiveness is evaluated through a usability assessment involving 21 SME users, employing a five-point Likert-scale instrument that reports positive perceptions across usability dimensions, with mean scores exceeding 3.7. These findings indicate that limited CRM functionalities, when structured through a clear analytical model, can effectively enhance relationship-oriented practices. The abstract explicitly situates the study within a single-SME deployment context, clarifying its practical scope and limitations. Overall, the study demonstrates that an analytically grounded, resource-conscious CRM implementation can provide actionable insights for SMEs seeking to strengthen customer engagement and retention without adopting complex or costly CRM solutions.